2022
DOI: 10.1111/acer.14761
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal alcohol exposure and mental health at midlife: A preliminary report on two longitudinal cohorts

Abstract: Background Although the effects of prenatal alcohol exposure (PAE) have been studied extensively, there is relatively little information available on adult mental health functioning among exposed individuals. The current study compares the self‐reported midlife mental health status of individuals who were prenatally exposed to alcohol and diagnosed in childhood with the effects of this exposure with that of unexposed individuals. Methods Participants (N = 292) were recruited from two longitudinal cohorts in At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 26 publications
(30 reference statements)
4
26
0
Order By: Relevance
“…Caution should be used in interpreting that PAE is protective against elevated arterial BP relative to a general population as both groups in this study had increased risk for hypertension when compared to large‐scale population databases. The National Health and Nutrition Examination Survey (NHANES) data collected between 2007 and 2010 indicated that 24.4% of males and 17.6% of females between 35 and 44 years have hypertension (Go et al, 2013) as compared to 70.3% of the Contrast group and 58.8% of the PAE group in this study, suggesting both groups have increased risk for vascular disease associated with their lower socioeconomic status and history of social adversity (Coles et al, 2022) when compared to the overall population of the United States. Even when the NHANES data are stratified by race (39.9% Black men and 42.7% Black women had hypertension after adjusting for age), participants in this study sample appear to carry increased risk for vascular disease.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Caution should be used in interpreting that PAE is protective against elevated arterial BP relative to a general population as both groups in this study had increased risk for hypertension when compared to large‐scale population databases. The National Health and Nutrition Examination Survey (NHANES) data collected between 2007 and 2010 indicated that 24.4% of males and 17.6% of females between 35 and 44 years have hypertension (Go et al, 2013) as compared to 70.3% of the Contrast group and 58.8% of the PAE group in this study, suggesting both groups have increased risk for vascular disease associated with their lower socioeconomic status and history of social adversity (Coles et al, 2022) when compared to the overall population of the United States. Even when the NHANES data are stratified by race (39.9% Black men and 42.7% Black women had hypertension after adjusting for age), participants in this study sample appear to carry increased risk for vascular disease.…”
Section: Discussionmentioning
confidence: 59%
“…Linking prenatal and early life exposures to later health outcomes has been a primary goal of those exploring the developmental origins of health and disease (DOHaD) hypothesis (Barker, 1990). The evidence in this study links PAE to mid-life health outcomes on vascular function using a prospective cohort initially identified while ease associated with their lower socioeconomic status and history of social adversity (Coles et al, 2022) when compared to the overall population of the United States. Even when the NHANES data are stratified by race (39.9% Black men and 42.7% Black women had hypertension after adjusting for age), participants in this study sample appear to carry increased risk for vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Early screening and trauma‐informed intervention are especially important to prevent later adverse life experiences associated with ACEs and maladaptive behavior. Recent literature suggests that environmental influences, including ACEs, mediate the effect of PAE on mental health problems in adulthood, emphasizing the importance of the environment in outcomes in adulthood (Coles et al, 2022). Additionally, people living with FASD are at higher risk for trouble with the law (Pei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…developmental delay versus stable weakness) [8 ▪ ,33,47]. On the basis of the emerging findings, prenatal alcohol exposure was associated with greater rates of mental health disorders in middle adulthood [48 ▪ ], including higher rates of depression, anxiety, bipolar disorder and attention-deficit/hyperactivity disorder, as well as increased suicidality [15 ▪▪ ]. These increased rates were mediated by greater environmental stressors, adverse childhood events and lower socioeconomic status, which are common for individuals with prenatal alcohol exposure [21].…”
Section: Conceptualizations Of Fetal Alcohol Spectrum Disorder and No...mentioning
confidence: 99%